Resveratrol reduces the spontaneous contractions of rabbit duodenum: El resveratrol reduce las contracciones espontaneas del duodeno de conejo - Santos-Fagundes, Diego; Gonzalo, Sergio; Grasa, Laura; Murillo, María Divina (Revista Científica de la Facultad de Ciencias Veterinarias, 2019)
Resveratrol, a natural polyphenol, is known for its antioxidant, anti-inflammatory, analgesic, antiviral, cardioprotective, neuroprotective and antiageing action. The aim of this study was to investigate the effect of resveratrol on the spontaneous contractions of rabbit duodenum (RD). Isolated segments of RD were suspended in an organ bath. Resveratrol (1 and 10 μM) reduced the amplitude but not the frequency of the spontaneous contractions in the longitudinal smooth muscle of RD. Bay K8644 (L-type Ca2+ channel activator) antagonized the inhibition of amplitude of spontaneous contractions induced by resveratrol. Apamin, charybdotoxin, glibenclamide and tetraethylamoniun did not modify the effect of resveratrol on duodenal muscle. It was conclude that the decrease of the spontaneous contractions induced by resveratrol would be mediated by Ca2+ channels.